Implementation of Online Learning Lessons in the Package C Program - Eddy, Guruh Suasana; Suryono, Yoyon (Universitas Negeri Semarang, 2019)
The use of internet media in the field of online education can create independence for students in learning. The purpose of this study is to obtain a full and in-depth description of the managers and tutors involved in implementing the online package C equality program organized by the Pioneer Community Learning Center. The research method uses this descriptive qualitative approach to describe the phenomenon experienced by the research subjects overall obtain information about the extent of the application of internet media in learning at school. The results of the online C learning package atÂ Pioneer community learning centers in Karanganyar run well and following the stages, this can be seen through the fulfillment of the stages starting from planning, implementation, to assessment. Constraints related to educators and students who are not familiar with the internet. The solution is to provide motivation and literacy training for online learning to students and their teachers. Regarding the constraints of facilities and infrastructure are still minimal and the need for additional facilities and infrastructure that supports online learning such as wi-fi point access and speed, number of wi-fi points, affordable rooms with internet access. The usefulness and benefits of this research are to provide direction for institutions in implementing online learning, especially non-formal education, which so far has been using conventional learning.